Liquidity Risk Management of Large U.S Banks during the Financial Crisis of 2007 – 2009 - Okocha, Ozioma (2014)
The Global Financial Crisis of 2007 – 2009 showed how vital liquidity was in the management of risks. The aftermath of the crisis saw the financial system as a whole taking better measures to ensure that liquidity was well managed across financial institutions. This paper provides empirical evidence on how banks managed their liquidity during the crisis. I find that core deposits and capital played an important role in the management of liquidity. Banks hoarded liquid assets to hedge themselves in anticipation to further losses. I also find that the size of the bank does not play a significant role in the management of bank liquidity risk.